(untitled) (London Journal of Research In Humanities and Social Sciences, 2023)
Geographical Indications are an intellectual property right characterized by being a product or service coming from a certain region, which, in the Brazilian case, has either become known as a center of production, extraction or manufacture, or because of its unique natural and human characteristics. Given this, the protection of the environment can emerge as one of its impotent functions, from the moment that, to maintain the status quo of natural factors, such as climate, soil, vegetation and many others that are proper to the region and essential for the effectiveness of the product or service, it is necessary to develop elements of environmental protection. Thus, this article intends to study and prove that Geographical Indications can be used for the protection of the environment through the promotion of public policies and environmental governance.